2016
DOI: 10.1002/slct.201600795
|View full text |Cite
|
Sign up to set email alerts
|

Phase and Shape Dependent Non-enzymatic Glucose Sensing Properties of Nickel Molybdate

Abstract: In this work, we demonstrate a facile low temperature synthesis approach to tune a and b-NiMoO 4 by controlling the urea concentration. Comparative non-enzymatic electrochemical glucose sensing properties of NiMoO 4 nanomaterials with a and b phases have been studied in detail. The mechanisms related to the phase and morphology transformation from a-NiMoO 4 nanoparticles to b-NiMoO 4 nanosheets are proposed and discussed by thoroughly characterizing the as-pre-pared materials. It is observed that the a-NiMoO 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…The CV study of both the NCO and NCO–Pd nanosheets was carried out with and without glucose analytes in 0.1 M of NaOH solution in the potential range of 0–0.7 V at a scan rate of 20 mV s –1 . Figure A clearly specifies the spectrum of the glucose-sensing activity for both without and with 100 μM glucose inside of the solution, and the distinguished peak obtained at 0.5 V is assigned as the oxidation peak of pure NCO. The detailed glucose-sensing mechanism of the NCO nanosheets has been explained in our previous study. Here, we outline the governing reactions …”
Section: Resultsmentioning
confidence: 96%
“…The CV study of both the NCO and NCO–Pd nanosheets was carried out with and without glucose analytes in 0.1 M of NaOH solution in the potential range of 0–0.7 V at a scan rate of 20 mV s –1 . Figure A clearly specifies the spectrum of the glucose-sensing activity for both without and with 100 μM glucose inside of the solution, and the distinguished peak obtained at 0.5 V is assigned as the oxidation peak of pure NCO. The detailed glucose-sensing mechanism of the NCO nanosheets has been explained in our previous study. Here, we outline the governing reactions …”
Section: Resultsmentioning
confidence: 96%
“…In addition, it has been reported that the NiMoO 4 has a phase-dependent selectivity and catalytic activity in the oxidative dehydrogenation of propane to propene 21 and glucose sensing property. 22 guide the rational design of novel NiMoO 4 -based electrocatalysts, it is essential that the phase-dependent catalytic activity of NiMoO 4 for the UOR process be identified. Herein, we synthesized NiMoO 4 •xH 2 O, α-NiMoO 4 , and β-NiMoO 4 to investigate the influence of phase on the electrocatalytic UOR process.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, as the NiMoO 4 catalysts in these reports consisted of mixtures of α-NiMoO 4 , β-NiMoO 4 , and NiMoO 4 · x H 2 O, , the role of the NiMoO 4 phase in the UOR activity remains ambiguous. In addition, it has been reported that the NiMoO 4 has a phase-dependent selectivity and catalytic activity in the oxidative dehydrogenation of propane to propene and glucose sensing property . Therefore, to guide the rational design of novel NiMoO 4 -based electrocatalysts, it is essential that the phase-dependent catalytic activity of NiMoO 4 for the UOR process be identified.…”
Section: Introductionmentioning
confidence: 99%
“…1b,c, respectively. And they have different coordination environments of Mo, namely, MoO6 for α-NiMoO4 and MoO4 for β-NiMoO4 11 . As a result, the transformation of the phase structures from NiMoO4•nH2O to NiMo(O) catalyst becomes vitally important for an in-depth analysis of the active sites, uncovering the nature of the HER.…”
Section: Introductionmentioning
confidence: 99%